Genome-wide associations for milk production and somatic cell score in Holstein-Friesian cattle in Ireland - BRADLEY, DANIEL GERARD MARY (My University, 2012)
Background: Contemporary dairy breeding goals have broadened to include, along with milk production traits, a number of non-production-related traits in an effort to improve the overall functionality of the dairy cow. Increased indirect selection for resistance to mastitis, one of the most important production-related diseases in the dairy sector, via selection for reduced somatic cell count has been part of these broadened goals. A number of genome-wide association studies have identified genetic variants associated with milk production traits and mastitis resistance, however the majority of these studies have been based on animals which were predominantly kept in confinement and fed a concentrate-based diet (i.e. high-input production systems). This genome-wide association study aims to detect associations using genotypic and phenotypic data from Irish Holstein-Friesian cattle fed predominantly grazed grass in a pasture-based production system (low-input).Results: Significant associations were detected for milk yield, fat yield, protein yield, fat percentage, protein percentage and somatic cell score using separate single-locus, frequentist and multi-locus, Bayesian approaches. These associations were detected using two separate populations of Holstein-Friesian sires and cows. In total, 1,529 and 37 associations were detected in the sires using a single SNP regression and a Bayesian method, respectively. There were 103 associations in common between the sires and cows across all the traits. As well as detecting associations within known QTL regions, a number of novel associations were detected; the most notable of these was a region of chromosome 13 associated with milk yield in the population of Holstein-Friesian sires.Conclusions: A total of 276 of novel SNPs were detected in the sires using a single SNP regression approach. Although obvious candidate genes may not be initially forthcoming, this study provides a preliminary framework upon which to identify the causal mechanisms underlying the various milk production traits and somatic cell score. Consequently this will deepen our understanding of how these traits are expressed. ? 2012 Meredith et al; licensee BioMed Central Ltd.
PUBLISHED
Keywords: article; cattle; chromosome 13; gene locus; genetic analysis; genetic association; genetic trait; genotype; grass; Ireland; milk production; milk yield; nonhuman; phenotype; scoring system; single nucleotide polymorphism; somatic cell; animal; Bayes theorem; cattle; cell count; dairying; female; genetics; lactation; milk; article; cattle; chromosome 13; gene locus; genetic analysis; genetic association; genetic trait; genotype; grass; Ireland; milk production; milk yield; nonhuman; phenotype; scoring system; single nucleotide polymorphism; somatic cell; animal; Bayes theorem; cattle; cell count; dairying; female; genetics; lactation; milk